Respuesta :
Answer:
[tex]\huge\boxed{\sf -3 (8x + 9)}[/tex]
Step-by-step explanation:
= -3(3x + 2) - 3(5x + 7)
Distribute the term
= -9x - 6 - 15x - 21
Combine like terms
= -9x - 15x - 6 - 21
Add or subtract
= -24x - 27
Take -3 common
= -3 (8x + 9)
[tex]\rule[225]{225}{2}[/tex]
Hope this helped!
~AH1807
Answer:
[tex]-24x-27[/tex]
Step-by-step explanation:
[tex]\underline{\mathrm{Simplify\:using\:distribution:}}[/tex]
[tex]-3(3x+2)-3(5x+7)[/tex]
[tex]=-9x-6-3\left(5x+7\right)[/tex]
[tex]=-9x-6-15x-21[/tex]
[tex]=-9x-15x-6-21[/tex]
[tex]=-9x-15x-27[/tex]
[tex]=-24x-27[/tex]